A Special Collection: Student Performance and Work-Based Learning - Lionel J. Beaulieu; Robert M. Gibbs (Journal of Research in Rural Education, 2005)
Despite evidence to the contrary, perceptions persist that rural America is marked by small and ineffective school systems, a place that falls short in its ability to adequately prepare students for college, and lacks supportive family and community environments for promoting educational success. These perceptions, often rooted in popular images of rural areas, are incongruent with the substantive improvements that much of rural America has witnessed over the course of the last few decades